A Chinese Command: A Story of Adventure in Eastern Seas - Collingwood, Harry, 1851-1922; Webb, Archibald, 1887-1944 (Salt Lake City, UT : Project Gutenberg, 2007)
"A Chinese Command: A Story of Adventure in Eastern Seas" by Harry Collingwood is an adventure novel written in the late 19th century. The narrative revolves around the character Murray Frobisher, a former Royal Navy officer, who faces a series of misfortunes after losing his ship. When approached by Captain John Drake, he is offered a chance to command a mission to deliver arms to Korean rebels, a dangerous venture packed with opportunities for both profit and peril. The opening of the novel establishes a somber yet suspenseful atmosphere as it introduces Frobisher, who is recovering from the loss of his ship and the subsequent damage to his reputation. He is depicted in a cottage at Kingston-on-Thames, awaiting news of his friend Dick Penryn. The narrative shifts focus to Frobisher's encounter with Captain Drake, who recruits him for the controversial mission of supplying arms to the rebels in Korea. This sets the stage for the unfolding story of adventure, danger, and moral dilemmas that Frobisher must navigate in the days to come. (This is an automatically generated summary.)
Release date is 2007-10-20
Produced by Nick Hodson of London, England
Keywords: Fiction; Sea stories; Adventure stories